2019
DOI: 10.1016/j.jjcc.2019.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Cryoablation for paroxysmal and persistent AF in patients with structural heart disease and preserved ejection fraction: Clinical outcomes from 1STOP, a multicenter observational project

Abstract: Background: Pulmonary vein isolation (PVI) is an accepted strategy for paroxysmal atrial fibrillation (PAF) and persistent AF (PerAF) ablation. Limited data are available on outcomes of cryoballoon (CB) PVI in patients with structural heart disease (SHD). The purpose is to assess the clinical efficacy of a single CB-PVI procedure in patients with PAF or PerAF who also have SHD. Methods: From April 2012, 460 AF patients with concomitant SHD underwent CB-PVI and were followed prospectively in the framework of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Patients with AF who had undergone CB‐PVI (using CB‐1, −2, −3, or −4) in 47 Italian institutions from April 2012 to April 2019 were prospectively followed through in‐hospital visits according to each center's clinical practice through the framework of the Italian ClinicalService and 1STOP project . In brief, the project (Clinical Trial Registration: NCT01007474) is a prospective examination of CB ablations conducted in Italian cardiology centers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with AF who had undergone CB‐PVI (using CB‐1, −2, −3, or −4) in 47 Italian institutions from April 2012 to April 2019 were prospectively followed through in‐hospital visits according to each center's clinical practice through the framework of the Italian ClinicalService and 1STOP project . In brief, the project (Clinical Trial Registration: NCT01007474) is a prospective examination of CB ablations conducted in Italian cardiology centers.…”
Section: Methodsmentioning
confidence: 99%
“…The description of the CB catheter ablation procedure has been previously published . In general, patients were treated with general anesthesia or conscious sedation during the procedure, and a heparin bolus was delivered at the time of the transseptal needle puncture into the left atrium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Discontinuation of vitamin K antagonists during the radiofrequency AF ablation procedure was reported to reduce the occurrence of periprocedural strokes and minor bleeding complications compared with bridging with low-molecular-weight heparin [6], and other studies using DOACs showed similar or better results [7][8][9]. Complications related to the vascular access sites are reported to be the most common complications during AF ablation [2] and the recent novel cryoballon [13] ablation with a large size sheath would increase the risk of access site complications.…”
Section: Discussionmentioning
confidence: 99%
“…Since the majority of AF triggers originate within the PVs, eliminating the source of AF has been established as the most important strategy for AF ablation [1][2][3]. Recently it has been reported that even patients with heart failure and structural heart disease have had good outcomes with catheter ablation for AF [4,5].…”
Section: Introductionmentioning
confidence: 99%